Performance analysis of a solar-powered maize sheller: production capacity and shelling efficiency - Hendradinata Hendradinata; Firdaus Firdaus; Toni Okviyanto; Tri Satya Ramadhoni; Muhammad Rizky Tolusha Putra; Muhammad Hafidzni Muttaqin; Taufikurrahman Taufikurrahman (Jurnal Polimesin, 2025)
Post-harvest mechanization is essential for improving productivity and reducing labor intensity in smallholder agriculture. This study aims to design and test the performance of a portable solar-powered maize sheller prototype developed as an environmentally friendly and cost-effective alternative for rural farmers. The research employed an engineering design approach consisting of mechanical and electrical system design, prototype fabrication, and performance testing by comparing solar-powered and grid-powered machines. The key parameters analyzed included shelling capacity, shelling efficiency, energy efficiency, grain damage rate, battery charging time, and operating cost. The results showed that the prototype achieved a shelling capacity of 65 kg/h with a shelling efficiency of 90% and a grain damage rate of 5%, comparable to grid-powered machines (91.4%) and higher than fossil fuel-based machines (85%). The prototype’s energy efficiency was recorded at 62.5%, lower than a grid-powered-based machine (80%) due to conversion losses in the panel, battery, and inverter, but still superior to fuel-based machines (35%). Economic analysis indicated that the solar-powered machine had the lowest operating cost, only IDR 5.3/kg, compared to grid electricity at IDR 7.3/kg and fuel-based machines at IDR 115/kg. Equipped with a 12 V–20 Ah battery and a 200 Wp solar panel, the machine can operate independently with a charging time of about six hours under optimal solar radiation. This research demonstrates the feasibility of solar energy utilization in maize shelling as an efficient, economical, and environmentally friendly solution.